Energy Efficient MANET Protocol Using Cross Layer Design for Military Applications - Rath, Mamata; Pattanayak, Binod Kumar; Pati, Bibudhedu (Defence Science Journal, 2016)
In military applications mobile adhoc network plays very important role because it is specifically designed network for on demand requirement and in situations where set up of physical network is not possible. This special type of network which takes control in infrastructure less communication handles serious challenges tactfully such as highly robust and dynamic military work stations, devices and smaller sub-networks in the battle field. Therefore there is a high demand of designing efficient routing protocols ensuring security and reliability for successful transmission of highly sensitive and confidential military information in defence networks. With this objective, a power efficient network layer routing protocol in the network for military application is designed and simulated using a new cross layer approach of design to increase reliability and network lifetime up to a greater extent.